2013
DOI: 10.15580/gjas.2013.3.031313523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cow Dung on the Growth and Development of Maize Crop

Abstract: Greenhouse and Field experiments were conducted at the Institute for Agricultural Research and Samaru College of Agriculture, Ahmadu Bello University, Zaria. The objectives of the experiments were to evaluate the combine effects of cow dung subjected to different management practices and Urea fertilizer on some Maize growth parameters and to observe the residual effects of the cow dung in the second year. The experiment was a factorial experiment, 3 management practices, 4 duration of storage, and 2 nitrogen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Application of fresh cow dung in four splits @ 2.5 t/ha each at 7, 15, 30 and 45 DAP (T 6 ) in scented rice had significant residual influence and produced the highest seed and stover yields of succeeding linseed. Similar results were also reported by Tanimu et al (2013). The increase in grain yield with T 6 treatment over T 1 (control), T 2 , T 3 , T 4 and T 5 was 34.4, 6.2, 6.1, 5.1 and 4.3 per cent.…”
Section: Effect On Succeeding Crop Linseedsupporting
confidence: 90%
“…Application of fresh cow dung in four splits @ 2.5 t/ha each at 7, 15, 30 and 45 DAP (T 6 ) in scented rice had significant residual influence and produced the highest seed and stover yields of succeeding linseed. Similar results were also reported by Tanimu et al (2013). The increase in grain yield with T 6 treatment over T 1 (control), T 2 , T 3 , T 4 and T 5 was 34.4, 6.2, 6.1, 5.1 and 4.3 per cent.…”
Section: Effect On Succeeding Crop Linseedsupporting
confidence: 90%
“…CD application at all levels increased leaf dry yield at harvest by 101 to 268% in acid soil and 98 to 278% in non-calcareous soil, respectively over control. Tanimu et al (2007) confirmed similar result in case of Maize. El-Dewiny et al (2006) showed that dry weight of radish and spinach plants increased with application of sewage sludge.…”
Section: Effect Of CD On Dry Weightsupporting
confidence: 85%
“…These results are almost similarly agreed with the findings of [19] in Albizia and [20] in Triticum. Improved seed germination might be attributed to the role of some important microorganism which influence in enhancing the easy availability of nitrogen, phosphorus and potassium in the soil and making available to the germinating seed with consequent enhancement in the cell metabolic activity resulting in higher germination [21][22]8]. According to [23] the nutrients present in organic fertilizers can be released only when its decomposition takes a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Its main objective of to create a balance between inter connected system of the soil organism, plants, animals and humans [7]. The choices of suitable forms of fertilizer of the crop growth of the plant are governed by local, natural condition and variation in soil and climate with regard to their suitability for crops cultivation [8]. Numerous test and experience have shown that farm yard manure with its long time effective nutrients on Agronomic Performance of Faba Bean (Vicia faba L.) and Pea (Pisum sativum L.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation